Removing policy based comparative advantage for energy intensive production. Necessary adjustments of the real exchange rate and industry structure - Torstein Bye; Erling Holmøy; Kim Massey Heide (Statistics Norway, Research Department, 2006)
National and international expansion of transmission networks and diminishing returns to scale in hydropower capacity expansion has raised the opportunity cost of electricity. The resulting changes in comparative advantage between industries have in many countries been counteracted by government assistance to energy intensive industries. A good example is the implicit electricity price subsidies offered to energy intensive manufacturing in Norway through the state owned power company Statkraft. We use firm data to assess the share of firms that will survive in the long run when these subsidies are removed, highlighting that large cost heterogeneity within the industries may imply diminishing returns to scale at the industry level. This feature is incorporated in a multisectoral CGE model, which is used to estimate the equilibrium adjustments of the industry structure and relative prices of removing the subsidies. Such a policy will lead to a less specialised industry structure and reduces gross trade. The positive public budget effect allows the government to cut other taxes, which fuels the real exchange rate depreciation necessary to meet the national budget constraint.
Keywords: D21; E23; E27; E62; F13; F18; F41; F43; 330; Industry policy; Comparative advantage; Structural change